First whisper of "The wind in the willows," by Kenneth Grahame, edited, with an introduction, by Elspeth Grahame. - Grahame, Kenneth, 1859-1932.; Grahame, Elspeth; Grahame, Kenneth, 1859-1932. (Philadelphia and New York, J. B. Lippincott company, 1945)
Contains the author's letters to his son on which "The wind in the willows" was based, and a hitherto unpublished
Keywords: Animals -- General book